Fractal Analysis of Structural and Phase Changes in the Metal of Welded Steam Pipe Joints - Garashchenko, Ya.; Glushko, A. V.; Kobets, O.; Harashchenko, O. (My University, 2021)
The research results of the ability to assess the boundaries of structural components’ geometric complexity, which are visible in a metallographic analysis of the metal samples of Welded Steam Pipe Joints, considering the operating time, are presented. The estimation of the complexity of grain boundaries was made based on a statistical analysis of fractal dimensions obtained by the cellular method for measuring the grain boundary length. The fractal analysis of microsection images is carried out using a developed program. The computer system was tested for several samples cut from sections of steam pipelines with different operating times, operated under conditions of creep and low-cycle fatigue. A comparative analysis of fractal dimensions of structural components’ boundaries in the microsections images of various metal sections with different operating times is carried out. The research and comparative analysis are carried out for the heataffected zone, base metal, weld, and substrate areas. As a result, the possibility of assessing the complexity of the boundaries of structural components in the steam pipelines metal and their welded joints was confirmed based on the analysis of statistical characteristics of the distribution of their fractal dimension.
Keywords: metallographic analysis; boundaries of structural components; geometrical complexity; fractal dimension